Pengertian Teologis Gereja Berdasarkan Kitab-Kitab Taurat dan Implementasinya untuk Masa Kini - Agustinus Djali; Maswati Daya (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: Since the church was founded, it has been faced with problems. The fathers have tried to lay the foundation of church teachings very fundamentally, but until today it seems that the problems have not disappeared, instead there are deviations in both doctrine and service that open up gaps for misguidance and cause church growth to stagnate. Therefore, the church should immediately introspect and return to its basic principles, namely "building a church based on the Bible, both the Old and New Testaments." The church in the time of Moses was an ancient church that was built by God in the beginning, it should be an example and role model for the church today. The purpose of this study: First: to study the nature of the church based on the books of the Torah so that today's congregation can have a theological understanding of churching so that they can apply it in their lives and congregational services. Second: to emphasize that the teachings about the true Church are also found in the books of the Torah, not only in the books of the New Testament. Third: to try to implement the theological understanding of the church based on the books of the Torah for today so that the congregation continues to strive to improve its teaching and performance in churching. This can be done through Theological Schools and seminars, sermons, and Bible studies, and cell groups in local churches.Keywords: Church of the Torah, Implementation.Abstrak: Sejak gereja berdiri terus diperhadapkan dengan masalah. Para bapa telah berusaha meletakkan fondasi ajaran gereja dengan sangat fundamental, namun sampai pada hari ini pun nampaknya masalah belum juga sirna, sebaliknya muncul penyelewengan baik dalam doktrin mapun pelayanannya yang membuka celah bagi penyesatan dan mengakibatkan pertumbuhan gereja mengalami stagnant. Maka gereja hendaklah segera mengintrospeksi diri serta kembali kepada azas dasarnya yakni “membangun gereja berdasarkan pada Alkitab baik PL maupun PB”Gereja pada jaman Musa merupakan gereja purba yang telah dibangun oleh Allah pada mulanya, seharusnya menjadi contoh dan teladan bagi gereja pada masa kini. Tujuan penelitian ini : Pertama: untuk mempelajari hakikat gereja berdasarkan kitab-kitab Taurat agar jemaat masa kini dapat memiliki suatu pemahaman teologis tentang bergereja sehingga dapat mengaplikasikannya dalam kehidupan dan pelayanan berjemaat. Kedua: untuk menegaskan bahwa ajaran tentang Gereja yang benar juga terdapat dalam kitab-kitab Taurat, bukan hanya pada kitab-kitab P B. Ketiga: berupaya mengimplementasikan pengertian teologis gereja berdasarkan kitab-kitab Taurat untuk masa kini sehingga jemaat terus berupaya meningkatkan, pengajaran dan kinerjanya dalam bergereja. Hal ini dapat dilaksanakan melalui Sekolah-Sekolah Teologi dan seminar-seminar, khotbah, serta penelahan Alkitab, komsel pada gereja lokal.Kata Kunci:Gereja kitab-kitab Taurat, Implementasi